KONTRIBUSI TRIPUSAT PENDIDIKAN UNTUK MENINGKATKAN MUTU PENDIDIKAN SEKOLAH DASAR DI KABUPATEN ACEH TAMIANG - Rusnani Rusnani; Siraj Siraj; Hera Yanti (Universitas Islam Negeri Sumatera Utara Medan, 2026)
This study aims to determine 1) How schools contribute to improving the quality of education 2) How families contribute to improving the quality of education 3) How communities contribute to improving the quality of education 4) How is the synergy between schools, families, and communities in supporting the improvement of the quality of education. This research method uses qualitative research. The subjects of this study are schools, families and communities. Data collection techniques use interviews, observation and documentation. While data analysis techniques use data reduction, data presentation, and drawing conclusions/verification. The results of the study indicate that the quality of basic education in Aceh Tamiang Regency can improve significantly if the relationship between elements of the Tripusat Pendidikan continues to be strengthened through a planned, trust-based collaboration strategy and supported by policies that facilitate educational partnerships.